Immunotherapy improves disease prognosis by affecting the tumor microenvironment: A bibliometric study - Wu, Xin; Deng, Zhen; Zhao, Qiangqiang (Frontiers in Immunology, 2022)
Background Immunotherapy has shown great potential for the treatment of multiple cancer and has been proven to be closely related to the tumor microenvironment. This article reveals collaborations and interactions among authors, nations, organizations, and periodicals assesses the knowledge base, and discovers hot tendencies and new topics associated with immunotherapy-tumor microenvironment (TME) research. Methods This article utilized bibliometrics and visual methods to provide a comprehensive overview of immunotherapy-TME research. Our team retrieved the WoSCC for research and reviews associated with immunotherapy and the tumor microenvironment. VOSviewer and Citespace were primarily used for literature measurement and knowledge graph analysis. Result All English articles and reviews on cancer immunotherapy effectiveness were collected, and 1,419 academic journals with 53,773 authors from 7,008 institutions in 92 countries/regions were found. Publications associated with immunotherapy-TME research were stably increasing. Frontiers of Immunology (n = 722) published the most papers on immunotherapy-TME, and Cancer Research (n = 6761) was the top co-cited journal. The published journals and co-cited journals focused on cancer and immunology fields. The League of European Research Universities (n = 978), Harvard University (n = 528), and the University of Texas system (n = 520) were the most productive institutions. Yang Liu (n = 34) and Topalian (n = 1978) ranked first among the top 10 scholars and co-cited scholars. Simultaneously, immunotherapy-TME researchers were involved in active collaborations. Elements of TME, the foundation of immunotherapy, and the application of immunotherapy in cancers represented the three principal aspects of immunotherapy-TME research. The latest hot spots are drug resistance, prognosis prediction, efficacy prediction, and m6A. Nanomedicine and m6A may be future hot topics. Future research in immunotherapy-TME may be directed at discovering how m6A modification affects tumor development by altering the tumor microenvironment and exploring how to enhance response or reduce drug resistance to immunotherapy by reversing or mediating the physicochemical properties of the TME. Conclusions M6A and nanomedicine are also emerging hotspots in time zone diagrams with high centrality, and prognosis prediction using bioinformatics based on the development of prediction technology may be another future research hotspot.